1991
DOI: 10.1210/endo-128-1-158
|View full text |Cite
|
Sign up to set email alerts
|

A New Role for Follicle-Stimulating Hormone in the Regulation of Calcium Flux in Sertoli Cells: Inhibition of Na+/Ca++ Exchange*

Abstract: Elucidation of mechanisms regulating intracellular calcium levels in steroidogenic tissues is important for understanding control of cellular function. We have previously described FSH receptor-mediated flux of 45Ca++ into cultured rat Sertoli cells and receptor-enriched proteoliposomes via voltage-sensitive and voltage-independent calcium channels. In the present study, we report heretofore unrecognized inhibitory effects of FSH on Na+/Ca++ exchange in these two systems. An outwardly directed Na+ gradient, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The calcium-phospholipid-dependent pathway in cultured immature rat Sertoli cells is not activated by FSH [25,26], and effects of FSH on cytosolic calcium levels are dependent on an influx of calcium. The mechanism of this influx is presently controversial: a) FSH-induced uptake of calcium is directly [6] or indirectly [27] coupled to a hypothetical FSH-operated calcium channel and b) it has been demonstrated that FSH hormone and FSH receptors modulate Na+/Ca 2 + exchange [28], c) bind calcium [29], or d) activate calcium channels [6,7]. Results with 4 5 Ca 2 + and fura-2 strongly suggest voltage-sensitive and voltage-independent calcium channels in freshly isolated [7] or cultured Sertoli cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…The calcium-phospholipid-dependent pathway in cultured immature rat Sertoli cells is not activated by FSH [25,26], and effects of FSH on cytosolic calcium levels are dependent on an influx of calcium. The mechanism of this influx is presently controversial: a) FSH-induced uptake of calcium is directly [6] or indirectly [27] coupled to a hypothetical FSH-operated calcium channel and b) it has been demonstrated that FSH hormone and FSH receptors modulate Na+/Ca 2 + exchange [28], c) bind calcium [29], or d) activate calcium channels [6,7]. Results with 4 5 Ca 2 + and fura-2 strongly suggest voltage-sensitive and voltage-independent calcium channels in freshly isolated [7] or cultured Sertoli cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Na + accumulation can also activate the Na + /Ca 2+ exchanger in a reverse mode where Ca 2+ is imported and Na + removed from the cell and both transporters contribute to cytosolic calcium accumulation. 43 All these conditions can give rise to a significant alteration of cellular behavior as exocytosis and/or nuclear transcription, which in turn may be a way to regulate cell metabolism in actively secreting cells. It has been shown previously that cAMP/PKA acts as a mediator of both 1,25D 3 genomic and nongenomic responses in a variety of cell systems.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It has been postulated that Na + /K + ATPase inhibition, and consequently Na + accumulation, evokes membrane depolarization and VDCC opening. Na + accumulation can also activate the Na + /Ca 2+ exchanger in a reverse mode where Ca 2+ is imported and Na + removed from the cell and both transporters contribute to cytosolic calcium accumulation . All these conditions can give rise to a significant alteration of cellular behavior as exocytosis and/or nuclear transcription, which in turn may be a way to regulate cell metabolism in actively secreting cells.…”
Section: Discussionmentioning
confidence: 99%
“…The hormonal sugar moiety makes specific interactions with the surface of the receptor cavity. While strongly-bonded low-density water was a barrier to movement of Ca" through the channel which has been proposed in the hFSH receptor, [26,27], weaklybonded water induced by accumulation of anionic groups, K+ and water, attracts Ca?' into the cavity, from which it diffuses through its transmembrane channel to elicit the biological response.…”
Section: Feds Lettersmentioning
confidence: 98%